The cumulative proportion of children receiving social care services in England: a whole population administrative data cohort study. - Matthew Jay; Louise Mc Grath-Lone; Rachel Pearson; Ruth Gilbert (International Journal of Population Data Science, 2022)
Objectives Children who receive social care services have high levels of need, but the proportion of the population they comprise is unknown. We aimed to estimate the cumulative proportion of children in England who ever become looked after (CLA) or placed on a child in need (CiN) plan by age 18.